2008
DOI: 10.1016/j.juro.2008.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Serum Carbonic Anhydrase 9 Level is Associated With Postoperative Recurrence of Conventional Renal Cell Cancer

Abstract: Our data suggest that serum carbonic anhydrase 9 is increased as the tumor progression occurs. A high carbonic anhydrase 9 level is associated with postoperative recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 13 publications
2
55
1
Order By: Relevance
“…Our results are in accordance with the study of Li et al, who first reported a significant association between serum CA IX and stage, tumor grade and size in patients with CCRCC. In their study of 91 patients, the mean value of serum CA IX in patients with metastatic CCRCC (216.68±67.02 pg/ ml) was significantly higher than that in localized CCRCC (91.65±13.29 pg/ml) (19). Similar CA IX values for CCRCC patients (126.1 pg/ml) with the same commercial ELISA kit for CA IX were reported by Zhou et al (20).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results are in accordance with the study of Li et al, who first reported a significant association between serum CA IX and stage, tumor grade and size in patients with CCRCC. In their study of 91 patients, the mean value of serum CA IX in patients with metastatic CCRCC (216.68±67.02 pg/ ml) was significantly higher than that in localized CCRCC (91.65±13.29 pg/ml) (19). Similar CA IX values for CCRCC patients (126.1 pg/ml) with the same commercial ELISA kit for CA IX were reported by Zhou et al (20).…”
Section: Discussionsupporting
confidence: 70%
“…However, the second study provides evidence that the estimated 5-year disease-free survival for patients with detectable CA9 mRNA in the peripheral blood was 39.5% in comparison with 88.1% for CA9-negative patients. Several studies have examined the potential clinical utility of s-CA IX in the serum from RCC patients for prognostic and predictive applications (18)(19)(20)(21)(22)(23). s-CA IX is a shorter form of CA IX (50/54 kDa) which is released into the culture medium or into the body fluids via a metalloprotease-dependent process regulated by TACE/ADAM17 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Our study reports that the plasma CAIX level in NSCLC patients is significantly higher than in healthy individuals (Po0.001). Nevertheless, we showed that the plasma CAIX detected in patients with NSCLC is much lower than CAIX concentrations described in renal cell carcinoma, because the very high constitutive HIF-1a levels in these latter tumours and also differences in CAIX expression depending on the cell type (Li et al, 2008). Increased levels of plasma CAIX have been reported only in urological cancers (Zavada et al, 2003;Li et al, 2008;Hyrsl et al, 2009).…”
Section: Discussionmentioning
confidence: 64%
“…Some molecules markers, such as CAIX (carbonic anhydrase IX), VEGF (vascular endothelial growth factor), GRP78 (glucose-regulated protein 78), CD146 had been found to be a powerful marker for the prognosis of RCC [15,16,17,18]. Circulating cfDNA, a biomarker that is easily accessible and preferably noninvasive, has been shown to have diagnostic and prognostic potential in RCC [12,19].…”
Section: Discussionmentioning
confidence: 99%